Pregnancy of undefined location - Carlos Moya Toneut; Miguel Román Sarduy Nápoles; Javier Cruz Rodríguez (Acta Médica del Centro)
Introduction: Pregnancy of undefined location is considered a worldwide public health problem. Objective: To reflect on pregnancy of undefined location and the challenge it represents for health professionals in contemporary society. Methods: A narrative bibliographic review was carried out including various texts, articles, printed and digital materials related to ectopic pregnancy. The databases and directories SciELO, LILACS, Latindex, Medline, were consulted using the keywords in Spanish and boolean operators, to expand the results: "pregnancy of undefined location", "ectopic pregnancy" AND "Consequences". 41 original and review articles were selected in the national and international context, in English and Spanish, published between 2000-2023. Conclusions: The possibility that a pregnancy of undefined location may result in an ectopic pregnancy leads to close follow-up of these patients and to reach a definitive diagnosis as soon as possible.